Molecular mechanism of Cuscutae semen–radix rehmanniae praeparata in relieving reproductive injury of male rats induced with tripterygium wilfordii multiglycosides: A tandem mass tag-based proteomics analysis - Han, Shanshan; Dai, Yanlin; Sun, Lihui; Xing, Yaping; Ding, Ying; Zhang, Xia; Xu, Shanshan (Frontiers in Pharmacology, 2023)
Background: We determined the effects of Semen Cuscutae–Radix Rehmanniae Praeparata on the protein levels in testicular tissues of rats gavaged with tripterygium wilfordii multiglycosides (GTW) and elucidated the molecular mechanism underlying Semen Cuscutae–Radix Rehmanniae Praeparata for relieving GTW-induced reproductive injury. Methods: A total of 21 male Sprague–Dawley rats were randomly divided into the control group, model group, and Semen Cuscutae–Radix Rehmanniae Praeparata group based on their body weights. The control group was given 10 mL·kg−1 of 0.9% normal saline by gavage daily. The model group (GTW group) was administered with 12 mg·kg-1 GTW by gavage daily. Semen Cuscutae–Radix Rehmanniae Praeparata group (the TSZSDH group) was administered with 1.56 g·kg−1 of Semen Cuscutae–Radix Rehmanniae Praeparata granules daily according to their model group dosing. The serum levels of luteinizing hormone, follicle-stimulating hormone, estradiol, and testosterone were measured after 12 weeks of continuous gavage, and the pathological lesion of testicular tissues was observed. Differentially expressed proteins were evaluated by quantitative proteomics and verified by western blotting (WB) and Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR). Results: Semen Cuscutae–Radix Rehmanniae Praeparata can effectively relieve pathological lesions of GTW-induced testicular tissues. A total of 216 differentially expressed proteins were identified in the TSZSDH group and model group. High-throughput proteomics revealed that differentially expressed proteins are closely associated with the peroxisome proliferator-activated receptor (PPAR) signaling pathway, protein digestion and absorption, and protein glycan pathway in cancer. Semen Cuscutae - Radix Rehmanniae Praeparata can significantly up-regulate the protein expressions of Acsl1, Plin1, Dbil5, Plin4, Col12a1, Col1a1, Col5a3, Col1a2, Dcn, so as to play a protective role on testicular tissues. Acsl1, Plin1, and PPARγ on the PPAR signaling pathway were verified by WB and RT-qPCR experiments, which were found to be consistent with the results of proteomics analysis. Conclusions: Semen Cuscutae and Radix Rehmanniae Praeparata may regulate the PPAR signaling pathway mediated Acsl1, Plin1 and PPARγ to reduce the testicular tissue damage of male rats caused by GTW.